RESEARCH ON THE HALAL MEAT TREND: CHALLENGE AND OPPORTUNITY AGENDA - Sukmaningrum , Puji Sucia; Maulana , Asep; Annisa , Rizka Fajri (I-iECONS e-proceedings, 2023)
The halal meat industry is one of the latest business trends in the world. The importance of halal meat is to maintain the continuity of the halal production process so that the quality and safety of meat is guaranteed until it reaches consumers. This paper aims to see the direction of research development of all papers with the title of halal meat published in reputable journals. This paper uses the Systematic Literature Review (SLR) method to provide a map of halal meat supply chain research trends. The development of halal meat research is still limited. This is evidenced from 2007 to 2023 by title only 48 articles indexed by Scopus by title. The author found that in Muslim countries halal is part of the belief in life. Whereas in non-Muslim countries, halal is seen as a brand component to increase market share. It is estimated that the demand for halal meat will continue to increase as the global Muslim population grows and because of the quality awareness of halal products. The results of this paper can provide specific directions for the government, researchers, and halal meat industry players. The government can improve and strengthen the regulation of the halal meat industry, for researchers as a reference for continuing research in the field of halal meat, and for halal meat industry players, consumer behavior towards halal meat can be an opportunity to increase market share.